THE POTENTIAL NEGATIVE IMPACT OF AIR LEAD POLLUTION ON CHILD DEVELOPMENT A PRELIMINARY STUDY IN TAMBAKLOROK, SEMARANG - Amin Husni (JOURNAL OF COASTAL DEVELOPMENT, 2000)
A review about potential negative impacts of air lead pollution especially on child development, based on a result ofa cross sectional study conducted in Tambaklorok-Semarang, an area with a very high air lead pollution, is reported. Subjects in the study were mothers who have lived more than three years in the area and their infants. The `subjects' characteristics, including age, height, weight, lead blood concentration (Pb- blood), Hemoglobin (Hb}, and the infants' developmental score were measured. The air lead concentration was measured for comparing to the air lead concentration reported by a previous research. Re-measurement ofthe Pb-air in August 1999 in Tambaklorok had a similar result with the Pb- air measured in August 1996 that was 100 times higher than that in a non·polluted Pb·air area. Statistical analysis showed that there was no signyicant correlation between the child Pb-blood and Matemal Pb-blood child ’s age, child ’s Hb, child ’s nutritional status that was calculated using Mass Body Index, and child development score, respectively. It seemed that child development was not influenced by the air lead exposure. The children were suffering fom anemia, but there was no signyicont correlation between the child Pb-blood and the child Hb.